LICHEN SIMPLEX CHRONICUS PADA REMAJA LAKI-LAKI USIA 13 TAHUN DENGAN RIWAYAT PRURITUS KRONIS PADA PERGELANGAN KAKI: LAPORAN KASUS - Dwi Hastuti; Septa Ayu Bungasari; Fathul Rizky (Kieraha Medical Journal, 2026)
ABSTRACT Lichen Simplex Chronicus (LSC) is a chronic inflammatory dermatosis characterized by skin lichenification resulting from a persistent itch–scratch cycle. Although commonly reported in adults, LSC is relatively uncommon in children and adolescents. This case report describes the clinical presentation, diagnosis, and management of LSC in a 13-year-old male adolescent. The patient presented with chronic pruritus on the anterior aspect of the left ankle that had persisted for several years and worsened during sweating. Repetitive scratching led to the development of a hyperpigmented lichenified plaque with scaling and excoriation. Based on clinical history and dermatological examination, a diagnosis of Lichen Simplex Chronicus was established. The patient was treated with topical corticosteroids, topical antipruritic agents, oral antihistamines, and behavioral education to avoid repetitive scratching. Follow-up evaluations at one and three weeks demonstrated marked improvement, including reduced pruritus, scaling, excoriation, and lichenification. This case highlights that LSC can occur in adolescents despite being more commonly observed in adults and may respond well to conservative therapy when diagnosed early and managed by effectively interrupting the itch–scratch cycle. Keywords : Lichen Simplex Chronicus, Adolescent, Lichenification, Neurodermatitis, Pruritus.